Therapist Interruptions: An Examination of Gender and Therapeutic Alliance in Couple Therapy. Issue 4 (8th August 2021) - Oka, Megan; Seedall, Ryan B.; Robinson, W. David; Walker, Jennifer; Tambling, Rachel R.; Anderson, Shayne
Abstract: Alliance is an important predictor of therapy outcomes, and studies examining in-therapy processes that contribute to alliance are needed. This study examines the relationship between interruptions and therapeutic alliance in couple therapy. First sessions of couple therapy from a university-based clinic were coded to examine the frequency of interruptions in therapy. Interruption frequency, interruption target, and subsequent measures of therapeutic alliance were examined to determine associations between those constructs. Results indicate a negative relationship between therapists interrupting men and male and female reports of alliance. Implications for therapeutic alliance and gender dynamics are discussed.